Influence of Parent’s Education on Parental Academic Involvement: The Impact of Parent's Education on Parental Academic Involvement (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Several researches showed that students with educated parents and high family social capital perform better in their career. The purpose of the study was to examine the influence of parental education on parental academic involvement at the secondary school level. The participants of the study were 615 secondary school students (Male 317, Female 298, aged 14-17 years) drawn from 15 secondary schools affiliated with CBSE board, session 2016-17 of Varanasi city, India Parental academic involvement was measured by students self-reported Perception of Parental Academic Involvement Scale (PPAIS) developed by investigator himself. PPAIS is consisted of 9 items and cronbach’s alpha estimate of reliability for the scale is 0.70 which is good and acceptable in the social science research situation. Univariate analysis of variance showed that mothers’ education has more positive influence on parental academic involvement than that of fathers’ education. Furthermore, this study did not find any gender effect with respect to mothers’ education as well as with fathers’ education.